Outcomes of Pembrolizumab plus chemotherapy for patients with metastatic non-squamous NSCLC: Real-world evidence - Irina Surovtsova; Felix J. F. Herth; Daria B. Kokh; Philipp Morakis (Pulmonology)
Background Pembrolizumab with chemotherapy (immunochemotherapy) has shown encouraging overall survival (OS) benefits in non-squamous mNSCLC, as demonstrated by the KEYNOTE-189 trial. However, randomised controlled trials may not fully capture the diversity of real-world patients. This study aims to evaluate immunochemotherapy outcomes in a real-world setting, including subgroups underrepresented in the KEYNOTE-189 trial.Methods Patients diagnosed with non-squamous mNSCLC 2011-2022 and recorded in Cancer Registry Database of the German Federal State Baden-Württemberg (BWCR), were analysed. OS was assessed using Kaplan-Meier and multivariable Cox models, adjusted for major clinical parameters. Results were compared with KEYNOTE-189.Results Among 2630 eligible cases, 1314 patients received chemotherapy alone and 1316 received immunochemotherapy. Median OS (mOS) was 14.1 months (95%CI: 13.1–15.4) for immunochemotherapy and 10.4 months (95%CI: 9.7–11.2) for chemotherapy alone, with an HR of 0.7 (95%CI: 0.64–0.77). A significant benefit was seen in M1c stage (HR 0.7, 95%CI: 0.63–0.79). No significant OS improvement was observed in patients with ECOG 2–3 or bone metastases.Conclusion This real-world evidence suggests that immunochemotherapy generally improves OS in mNSCLC. Subgroup analysis showed no survival benefit for patients with ECOG >1 or bone metastasis, but a benefit for patients with M1c stage.